Halkla ilişkilerde imaj olgusu - Coşkun, Sibel (My University, 2002)
Gündelik yaşantımızda farklılığın, yeniliğin, bireyselliğin bir göstergesi olarak sıkça kullanıp, duyduğumuz imaj sözcüğü hangi anlamları içermektedir? Kuruluşların da imajları var mıdır? Bir disiplin dalı olan halkla ilişkilerin imaj oluşumundaki rolü nedir? Bu çalışmayla, sıralanan soruların yanıtlanması amaçlanmıştır. Çalışmanın temel varsayımı; halkla ilişkilerin, tüketim kültürü söylemini pekiştirici imajlar oluşturduğudur. Halkla ilişkiler, çeşitli yöntemler kullanarak kuruluşlara ve kişilere imajlar oluştururken, bir yandan da tüketimin devamlılığını sağlamaktadır. Name and Surname: Sibel COŞKUN Graduate Program: Communication Sciences Science: Public Relations Thesis: Melda Cinman Şimşek Form of Thesis and Date: Master of Arts - November 2002 Key Words: Image, Public Relations, Consumption

What is the meaning of the word image, which we heard and use often as a sign of differences, innovations and individualism? Do organizations have images too? What is the role of public relations in forming images as a discipline field? This study aims to answer these questions. The main hypothesis of the study is that the practices of public relations form images that intensifies discourse of consumption culture. Public relations provides continuity of consuming, while it forms images for organizations and people by using various methods.
Keywords: Halkla ilişkiler; Halkla İlişkiler